Development of an Online Multilingual Educational Programme for Parents of Dual-Career Athletes: A Participatory Design - Laura Capranica; Laura Capranica; Flavia Guidotti; Carlos Gonçalves; Laurence Blondel; Matteo Bovis; Rute Costa; Nadine Debois; Antonio Figueiredo; Ciaran MacDonncha; Ciaran MacDonncha; Viktorija Pecnikar-Oblak; et al. (Frontiers in Psychology, 2022)
There is a need for educational support structures to empower parents in sustaining talented athletes pursuing academic and sports careers (e. g., dual career). The present work describes the participatory design used to develop a series of educational resources and the subsequent iterations used to evaluate the content of the EMPATIA online education programme for parents of dual-career athletes. Following an ethnographic approach, the project team (18 dual-career experts) engaged in four iterations (i.e., rounds) planned to develop (rounds 1 and 2) educational material from preliminary evidence (systematic literature review) and eminence (focus groups and concept mapping) knowledge and to evaluate the educational programme (round 3 and 4) engaging end users (n = 76) and other stakeholders (9 dual-career experts). The EMPATIA programme was developed and organized in four modules labeled after macro-aspects, parents could ask about dual career: “Why” (the definition and challenges of dual career for athletes and their parents), “What” (insights, guidelines, and suggestions on the parental role in support of student-athletes), “How” (practical advice on planning dual career at sports and academic levels, and post-sports careers), and “Where” (finding legal information or counseling on dual career). Despite overall positive evaluations of the programme, parents of dual-career athletes attributed higher scores with respect to those of dual-career experts. The participatory approach presented in this work enables developers to apply a systematic and multidisciplinary approach toward the creation of educational programmes for parents. The cooperation among dual-career researchers, experts from high-performance centers, Olympic bodies, sports clubs, and parents of elite student-athletes of different sports and nationalities created an educational programme suitable for end users to support parenting athletes in combining their sports and academic careers.